Janus mucosal dressing with a tough and adhesive hydrogel based on synergistic effects of gelatin, polydopamine, and nano-clay. (1st September 2022) - An, Heng; Gu, Zhen; Zhou, Liping; Liu, Songyang; Li, Ci; Zhang, Meng; Xu, Yongxiang; Zhang, Peixun; Wen, Yongqiang
Abstract: There are many problems and challenges related to the treatment of highly prevalent oral mucosal diseases and oral drug delivery because of a large amount of saliva present in the oral cavity, the accompanying oral movements, and unconscious swallowing in the mouth. Therefore, an ideal oral dressing should possess stable adhesion and superior tough strength in the oral cavity. However, this fundamental requirement greatly limits the use of synthetic adhesive dressings for oral dressings. Here, we developed a mussel-inspired Janus gelatin-polydopamine-nano-clay (GPC) hydrogel with controlled adhesion and toughness through the synergistic physical and chemical interaction of gelatin (Gel), nano-clay, and dopamine (DA). The hydrogel not only exhibits strong wet adhesion force (63 kPa) but also has high toughness (1026 ± 100 J m −3 ). Interfacial adhesion of hydrogels is achieved by modulating the interaction of catechol groups of the hydrogel with specific functional groups (e.g., NH2, SH, OH, and COOH) on the tissue surface. The matrix dissipation of the hydrogel is regulated by physical crosslinking of gelatin, chemical crosslinking of gelatin with polydopamine (Michael addition and Schiff base formation), and nano-clay-induced constraint of the molecular chain. In addition, the GPC hydrogel shows high cell affinity and favors cell adhesion and proliferation. The hydrogel's instant and strong mucoadhesive properties provide a long-lasting therapeutic effect of the drug, thereby enhancing the healing of oral ulcers. Therefore, mussel-inspired wet-adhesion Janus GPC hydrogels can be used as a platform for mucosal dressing and drug delivery systems. Statement of significance: It is a great challenge to treat oral mucosal diseases due to the large amount of saliva present in the oral cavity, the accompanying oral movements, unconscious swallowing, and flushing of drugs in the mouth. To overcome the significant limitations of clinical bioadhesives, such as weakness, toxicity, and poor usage, in the present study, we developed a simple method through the synergistic effects of gelatin, polydopamine, and nano-clay to prepare an optimal mucosal dressing (Janus GPC) that integrates Janus, adhesion, toughness, and drug release property. It fits effectively in the mouth, resists saliva flushing and oral movements, provides oral drug delivery, and reduces patient discomfort. The Janus GPC adhesive hydrogels have great commercial potential to support further the development of innovative therapies for oral mucosal diseases. Graphical abstract: Image, graphical abstract